Coagulase gene polymorphisms detected by PCR in Staphylococcus aureus isolated from subclinical bovine mastitis in Turkey - Karahan, Murat; Çetinkaya, Burhan (Elsevier Sci Ltd, 2007)
The genetic relatedness of coagulase (coa) positive Staphylococcus aureus isolated from cows with subclinical mastitis in Turkey was investigated by polymerase chain reaction (PCR)-based restriction fragment length polymorphism (RFLP) analysis. Among 700 milk samples positive in the California Mastitis Test (CMT), species specific PCR identified 200 (28.6%) isolates as S. aureus and 161 (80.5%) of these isolates were positive for the 3' end of the coa gene by PCR. Most isolates (n = 135, 83.9%) produced a single band on coa PCR, with molecular sizes ranging from 500 to 1400 bp, whereas a small number of isolates (n = 26, 16.1%) yielded two amplification products. Coa RFLP analysis using AluI and Hin6I revealed 23 and 22 band patterns, respectively. The detection of double bands by coa PCR, previously reported in human isolates, suggests that milking personnel can play a role in the transmission of S. aureus. (c) 2006 Elsevier Ltd. All rights reserved.
Keywords: Staphylococcus aureus; cattle; mastitis; coa gene; PCR-RFLP